Diversity and Temporal Dynamics of the Epiphytic Bacterial Communities Associated with the Canopy-Forming Seaweed Cystoseira compressa (Esper) Gerloff and Nizamuddin - Mancuso, Francesco P.; D'Hondt, Sofie; Willems, Anne; Airoldi, Laura; De Clerck, Olivier (Frontiers in Microbiology, 2016)
Canopy-forming seaweed species of the genus Cystoseira form diverse and productive habitats along temperate rocky coasts of the Mediterranean Sea. Despite numerous studies on the rich macrofauna and flora associated with Cystoseira spp., there is little knowledge about the epiphytic bacteria. We analyzed bacterial populations associated with canopies of Cystoseira compressa, over an annual vegetative cycle (May-October), and their relationships with the bacterial populations in the surrounding seawater, at intertidal rocky shores in Vasto (Chieti - Italy). The bacterial diversity was assessed using Illumina Miseq sequences of V1-V3 hypervariable regions of 16S rRNA gene. C. compressa bacterial community was dominated by sequences of Proteobacteria and Bacteroidetes, Verrucomicrobia, Actinobacteria and Cyanobacteria especially of the Rhodobacteriaceae, Flavobacteriaceae, Sapropiraceae, Verrucomicrobiaceae and Phyllobacteriaceae families. Seawater libraries were also dominated by Proteobacteria and Bacteroidetes sequences, especially of the Candidatus Pelagibacter (SAR11) and Rhodobacteriaceae families, but were shown to be clearly distinct from C. compressa libraries with only few species in common between the two habitats. We observed a clear successional pattern in the epiphytic bacteria of C. compressa over time. These variations were characterized by gradual addition of OTUs (Verrucomicrobia, Actinobacteria and SR1) to the community over a growing season, indicative of a temporal gradient, rather than a radical reorganization of the bacterial community. Moreover, we also found an increase in abundance over time of Rhodobacteraceae, comprising six potential pathogenic genera, Ruegeria, Nautella, Aquimarina, Loktanella, Saprospira and Phaeobacter which seemed to be associated to aged thalli of C. compressa. These bacteria could have the potential to affect the health and ecology of the algae, suggesting the hypothesis of a possible, but still unexplored, role of the microbial communities in contributing to the extensive ongoing declines of populations of Cystoseira spp. in the Mediterranean Sea.